Millimetre-long transport of photogenerated carriers in topological insulators - Yasen Hou (Nature Portfolio, 2019)
Exciton condensation may emerge at room temperature in topological materials with strong Coulomb interactions and vanishing electron effective mass. Here, Hou et al. report the formation of excitons in Bi2-x Sb x Se3 nanoribbons, which can transport over hundreds of micrometres before recombination up to 40 K, further implying exciton condensation.